The effects of statins on pulmonary artery pressure in patients with chronic obstructive pulmonary disease: A randomized controlled trial - Anahita Arian; Sayyed Gholamreza Mortazavi Moghadam; Toba Kazemi; Morteza Hajihosseini (Wolters Kluwer Medknow Publications, 2017)
Objective: Pulmonary hypertension is a serious complication in patients suffering from chronic obstructive pulmonary disease (COPD). The aim of this study is to investigate the effects of atorvastatin in reducing pulmonary arterial pressure in COPD patients. Methods: This double-blind, randomized trial was conducted on 42 known cases of COPD with systolic pulmonary arterial pressure of more than 25 mmHg. The patients were randomly assigned into two groups, 21 patients with atorvastatin treatment (40 mg/daily for 6 months) and 21 patients without receiving atorvastatin. All the patients participated voluntarily and provided written informed consent. The trial was registered in the Iranian Registry of Clinical Trials. Pulmonary pressure was also anticipated by Doppler echocardiography with peak pressure gradient of tricuspid regurgitation. Both groups were tested with echocardiography to measure systolic pulmonary pressure at baseline and posttreatment. Statistical analysis includes Chi-square, Student's t-test, and Wilcoxon test. P < 0.05 was considered statistically significant. Findings: The mean age was 65.8 ± 11.5 years for atorvastatin group and 63.7 ± 7.6 years for control group (P = 0.45). Baseline and posttreatment mean systolic pulmonary artery pressure (PAP) levels in the atorvastatin group were 48.9 ± 3.3 and 38.4 ± 1.9 mmHg, respectively (P = 0.007). In the control group, mean systolic PAP levels at baseline and 6 months later were 45.6 ± 3.1 and 38.9 ± 2.4 mmHg, respectively (P = 0.073). The patients treated with atorvastatin showed significant decrease in total cholesterol (P = 0.001) and low-density lipoprotein cholesterol (P = 0.008). Conclusion: A 40 mg dose of atorvastatin daily for 6 months may have beneficial effects in reducing PAP in patients with COPD. Further studies are necessary to find long-term effects of statins in COPD patients.